Home care as reablement or enabling arrangements? An exploration of the precarious dependencies in living with functional decline. Issue 7 (24th April 2019) - Bødker, Malene N.; Christensen, Ulla; Langstrup, Henriette
Abstract: The threat to welfare societies posed by population ageing has urged high‐income countries to rethink the provision of social and healthcare services for the ageing population. One widely implemented policy solution is 'reablement': short‐term home‐based training programmes focusing on re‐enabling older people to carry out activities of daily living independently. Drawing on empirical material from multisited ethnographic fieldwork of reablement practices in a Danish municipality we explore how the assumptions about independence embedded in the concept's linguistic parts – 're', 'able' and 'ment' – map onto lives characterised by functional decline. We find that home care applicants: (i) are often too deeply dependent on the capacities of others in order to have their independence restored; (ii) negotiate individual meanings of independence to maintain their identity as able human beings; and (iii) might possibly gain new capacities through reablement, yet these are not individual and stable achievements, but rather temporary effects of the care relations with eldercare professionals. Rather than reablement we, therefore, suggest the term 'enabling arrangements' as more appropriate for capturing independence as a distributed, negotiated and continuous accomplishment. Finally, we discuss the practical and ethical implications of this term.